Hubungan Perawatan yang Tidak Memadai dengan Kejadian Stunting di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung - Mutiara Ayu Daniati; Rilyani Rilyani; Riska Wandini (Malahayati Nursing Journal, 2025)
ABSTRACT One of the inadequate treatments is parenting, where parenting plays an important role in the emergence of stunting in children. The prevalence of stunting in Bandar Lampung City in 2021 with the highest order is in the Karang City Health Center with prevalence (24.2%), the New Arrangement Health Center (20.4%) and the Way Laga Health Center (17.5%). It is known that the relationship between inadequate care and the incidence of stunting in the working area of the Karang Bandar Lampung Inpatient Health Center. This study uses a quantitative analytic design approachcross sectional. The population in this study were toddlers aged 36-59 months who were in the working area of the Karang City Health Center as many as 755 toddlers with a total sample of 263 respondents. Sampling using techniquesAccidental Sampling. Data analysis using statistical testschi square. This study used a chi-square analysis test which obtained the results of an analysis of the relationship between feeding parenting and the incidence of stunting obtained a p-value of 0.006 (0.05), there was no relationship between stimulus and children's activity and the incidence of stunting obtained a p-value 0.65 ( 0.05), and there is a relationship between household feeding distribution and stunting, with a p-value of 0.000 (0.05). There is a relationship between feeding parenting and the incidence of stunting, there is a relationship between child stimulus activity and the incidence of stunting and there is a relationship between the distribution of household feeding and the incidence of stunting. It is recommended to be able to pay attention to parenting patterns in feeding children. It does not stop at feeding parenting, but attention must also be paid to children's stimulus activity as well as household food distribution. Because these three aspects are very important in the period of development growth of children so that there are no stunting problems. Keywords: Stunting, Inadequate Care, Children.  ABSTRAK Perawatan yang tidak memadai salah satunya adalah pola asuh, dimana pola asuh berperan penting dalam munculnya stunting pada anak. Prevalensi stunting di Kota Bandar Lampung pada tahun 2021 dengan urutan tertinggi terdapat di puskesmas Kota Karang dengan prevalensi (24,2%), puskesmas Susunan Baru (20,4%) dan puskesmas Way Laga (17,5%). Diketahui hubungan perawatan yang tidak memadai kejadian stunting di wilayah kerja Puskesmas Rawat Inap Kota Karang Bandar Lampung. Penelitian ini menggunakan desain analitik kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah balita usia 36-59 bulan yang berada di wilayah kerja Puskesmas Kota Karang sebanyak 755 balita dengan jumlah sampel 263 responden. Pengambilan sampel menggunakan teknik Accidental Sampling. Analisis data menggunakan uji statistic chi-square. Penelitian ini menggunakan uji analisis chi-square yang didapatkan dengan hasil analisis hubungan antara pola asuh pemberian makan dengan kejadian stunting didapatkan p-value 0,006 (0,05),tidak terdapat antara hubungan antara stimulus dan aktivitas anak dengan kejadian stunting didapatkan p-value 0,65 (0,05),dan terdapat hubungan antara distribusi pemberian makan rumah tangga dengan kejadian stunting didapatkan p-value 0,000 (0,05). Ada hubungan antara pola asuh pemberian makan dengan kejadian stunting, ada hubungan antara stimulus aktivitas anak dengan kejadian stunting dan ada hubungan antara distribusi pemberian makan rumah tangga dengan kejadian stunting. Disarankan untuk dapat memperhatikan pola asuh dalam pemberian makanan pada anak. Tidak berhenti di pola asuh pemberian makan tetapi harus di perhatikan juga dalam stimulus aktivitas anak dan juga distribusi makanan rumah tangga. Karna ketiga aspek tersebut sangat penting dalam masa perkembangan pertumbuhan anak agar tidak terjadinya masalah stunting. Kata Kunci: Stunting, Perawatan Tidak Memadai,Anak.